Ecosystem health river basin; a preliminary case study at Semerak River Basin, Kelantan on the water quality perspective - Ishak, Nurul Syahiirah (Universiti Sains Malaysia, 2014)
Water quality of Semerak River Basin (SRB), Pasir Puteh Kelantan is affected by the agricultural development and accommodation of crowded and heavy population. The industrial and domestic activities also actively carried out within this area. The aims of this study were to determine the water quality of the river basin based on several parameters of International Water Quality Index (WQI) and also to identify the causes of water quality on Semerak River based on the changes of land used. Besides that, this study was also carried out to identify the level of ecosystem health in SRB based on river water quality. Sampling was conducted on a weekly basis starting from December 2013 until February 2014. For every data collection, water sample was collected once per sampling station for every week. In this study, the relationship between water quality parameters, e.g. Biochemical Oxygen Demand (BOD), Dissolved Oxygen (DO), Chemical Oxygen Demand (COD), Ammoniacal Nitrogen (NH3-N), Total Suspended Solids (TSS), pH and sampling stations was identified by analyzing the statistical test. From the result, total mean value for SRB; DO (9.30 mg/L), BOD (4.42 mg/L), COD (60.02 mg/L), NH3-N (0.28 mg/L), TSS ( 16.39 mg/L), and pH (5.79). The parameters were examined by correlation analysis of ANOVA test with significant level (p< 0.05). There were significant differences for all parameters except for COD, at which DO, BOD, NH3-N and temperature was significant with p= 0.001, while TSS was significant at p= 0.010. The results of water quality for all sampling stations were classified under Class III. WQI for SRB were also categorized under Class III and considered as polluted for whole river basin. Based on this study it can be concluded that the water condition of SRB is slightly disturbed. In the near future, more land will be developed, due to increase in infrastructure development, population and industrial activities that will consequently increase the population level in Semerak River. Hence, effective pollution control on river basin management and new analysis on relationship between land use and water quality should be implemented to improve the quality of the water in the future.